2020
DOI: 10.12964/jsst.20002
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Research Trends in Sandplay Therapy in Korea (2009-2018)

Abstract: The aim of this study was to investigate research trends in sandplay therapy in South Korea. Thus we analyzed 205 Korean research papers published between 2009 and 2018. We grouped our results into five categories using the research trend analysis method. Those categories were research topic, subject, method, and characteristics of sandplay therapy. The results reveal the current status and limitations of sandplay research. These also suggest future research directions for sandplay therapists and researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Sandplay therapy is an effective method to improve college students' unhealthy mental states, such as interpersonal maladjustment, anxiety, and attention deficits. Group sandplay therapy takes the group as the activity unit, and sandplay therapy in the group situation can promote interpersonal interaction, which has been proved to be effective [ 15 ]. Students in vocational colleges are in adolescence, and their physiological development has been basically mature, but their psychology is still immature, their ideas are also in the social survival of the fittest, and fair competition is constantly being tempered and tempered [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sandplay therapy is an effective method to improve college students' unhealthy mental states, such as interpersonal maladjustment, anxiety, and attention deficits. Group sandplay therapy takes the group as the activity unit, and sandplay therapy in the group situation can promote interpersonal interaction, which has been proved to be effective [ 15 ]. Students in vocational colleges are in adolescence, and their physiological development has been basically mature, but their psychology is still immature, their ideas are also in the social survival of the fittest, and fair competition is constantly being tempered and tempered [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…This meta-analysis did not study the cognitive dimensions of treatment outcomes. Several studies assessed in the process of this meta-analysis indicated that research subjects also demonstrated improvements in cognition, academic achievement, and/or brain functioning after sandplay therapy treatment (Foo et al, 2020;Foo & Pratiwi, 2021;Lee & Jang, 2013;Lee et al, 2018;Lee & Jang, 2015;Unnsteinsdo ´ttir, 2012). Cognitive and related dimensions might be addressed in further research.…”
Section: Limitations and Suggestions For Further Researchmentioning
confidence: 93%
“…Research in sandplay therapy has historically focused on theoretical and qualitative explorations emphasizing case study and multiple case study designs. However, over the past 12 years, there has been a sharp increase in quantitative studies demonstrating the efficacy of sandplay therapy utilizing pre–post and quasi-experimental research designs, as well as a significant number of randomized controlled trials (RCT; Ahn et al, 2020; Roesler, 2019). With this growing body of research, there is a pressing need to examine the cumulative results of sandplay therapy through meta-analysis (Wiersma, 2019).…”
mentioning
confidence: 99%
“…Study subjects were confined to adults between the ages of 19 and 64. Children and adolescents, who were subjects of prior studies, and the elderly, who were not part of any study included in A Study on Research Trends in Sandplay Therapy in Korea (2009Korea ( -2018 by Ahn et al (2020), were excluded. The specified intervention method was sandplay therapy.…”
Section: Data Collection and Selectionmentioning
confidence: 99%